Diagnostic value of combining immunostaining for CD3 and nuclear morphometry in mycosis fungoides. Issue 2 (11th May 2007) - Lira, M; Schenka, A A; Magna, L A; Cotta, A C; Cintra, M L; de Souza, E M; Brousset, P; Vassallo, J
Abstract : Background: Mycosis fungoides (MF) is the most common skin lymphoid neoplasm. In initial stages, differential diagnosis of MF from other benign dermal lymphoid infiltrates (BDLI) may be impossible on morphological basis alone. In previous studies, only deletion of CD7 in MF proved to be of diagnostic help, but not the ratio between immunoexpression of CD4 and CD8. Methods: 30 cases of MF and 11 cases of BDLI were analysed, in order to compare morphometric parameters, which could be of diagnostic aid. As CD7 is frequently deleted in MF, immunohistochemical detection of T-cells was made using an antibody to CD3. Images of 100 CD3-positive cells per case in both groups were captured and analysed using a simple computer program for nuclear perimeter, area, diameter and nuclear contour index. Results: All parameters showed statistically significant higher values for MF. Area was the variable with the strongest discriminating power between the two groups of patients. Thus even if morphological evaluation is not accurate to distinguish benign versus malignant dermal lymphoid infiltrates, due to the variability of size and shape of these cells, a more sensitive method promptly shows this difference. Conclusion: Results suggest that morphometry of CD3-positive lymphoid cells may add valuable information in the differential diagnosis of MF and benign dermatoses.